The Comprehensive Systematic Review of Management of Hypertensive Emergencies with Neurological Involvement - Aulia Olviana (International Medical Journal Corp. Ltd, 2026)
Introduction: Hypertensive emergencies with neurological involvement, particularly intracerebral hemorrhage (ICH), present a therapeutic challenge where rapid blood pressure (BP) reduction must balance hematoma expansion prevention against cerebral ischemia risk. This review synthesizes evidence on management strategies. Methods: A systematic screening of sources identified 80 studies meeting predefined criteria: adult populations with hypertensive emergency and acute neurological symptoms, examining pharmacological or surgical interventions with clinical outcome reporting. Included studies comprised randomized controlled trials, cohort studies, and post-hoc analyses of major trials (INTERACT2, ATACH-2). Results: Intensive systolic BP (SBP) reduction to <140 mmHg reduced hematoma expansion but showed divergent functional outcomes: INTERACT2 demonstrated ordinal benefit (OR 0.87, p=0.04) while ATACH-2 was neutral. Pooled analysis revealed a J-shaped relationship: SBP reduction of 55-85 mmHg within 2 hours optimized outcomes, while reductions >70 mmHg reversed benefit (OR for unfavorable outcome increased) and increased acute kidney injury (OR 2.00, p<0.05). In patients with initial SBP ≥220 mmHg, intensive reduction caused excess neurological deterioration (15.5% vs. 6.8%, p=0.04). Minimally invasive surgery (endoscopy/aspiration) achieved superior 6-month functional outcomes (mRS 0-2: 33.3% and 32.7% vs. 22.2% for craniotomy, p=0.017). Urapidil produced greater BP reduction and better 1-month neurological scores than nitroprusside (p<0.05). Discussion: The apparent INTERACT2-ATACH-2 discrepancy is explained by differential baseline SBP, reduction magnitude crossing into harmful J-curve territory, and agent-specific effects. Optimal management requires individualized SBP reduction targets (55-85 mmHg range) with avoidance of excessive hypotension, particularly in severe ICH or extremely elevated SBP. Conclusion: Intensive BP reduction is beneficial when magnitude is titrated to baseline SBP, with an optimal reduction of 55-85 mmHg. Minimally invasive surgery improves outcomes in deep hemorrhages. Urapidil shows superior efficacy.